Effectiveness of Information and Communication Programmes for Children with Special Educational Needs in the Context of Speech Development - Chekan, Oksana; Barna, Khrystyna; Forostian, Olha; Sokolova, Hanna; Raievska, Yana (International Journal of Child Health and Nutrition, 2024)
The work aims to determine the effectiveness of information and communication programs for special educational needs (SENs) in the context of speech development. The aim was achieved through the use of general theoretical methods of analysis, observations, and calculations of the ranking factor, efficiency coefficient, and Phillips correlation coefficient. It was established that the most effective approaches for the development of children's speech are the use of information technologies (2.5), social interaction (2.37), and group approach (2.25). Results: The results provided grounds for developing a speech and general development program for children aged 4 to 7. The program provided for the creation of mind maps, provision of joint reading, performance of educational songs, and development of speech in accordance with the specified topic. Training became possible due to the use of modern technologies, namely the applications MindMeister, Digital Inclusion, and speech synthesis from Google and YouTube. It was established that the developed program had a positive effect on the improvement of children’s phonetic speech compared to the results at the beginning of the study. Conclusions: The practical significance of the work implies the possibility of using the developed program for speech correction among a larger number of children. Prospects: Research prospects are related to elaborating speech development mechanisms depending on the degree of speech impairment.